From the Research Cycle to the People Cycle: Humanizing Digital Curation - Lauren Geiger; Kathryn New; Carolina Siniscalchi (International Journal of Digital Curation)
In this paper, we argue that digital curators need to move beyond explaining technical jargon and workflows to collaborate with researchers to meet them where they are at when educating them on digital curation skills. At Mississippi State University, we teach students, staff, and faculty about digital curation by connecting it to the skills they already have and cut out complicated jargon to get to what really matters: knowing how to manage data so it can be understood and used. We focus our pedagogy on strengthening the curation skills they already have and bringing in newer concepts by framing them within areas they are already familiar with. We hope that by adding a people lifecycle to the research lifecycle, we can empower our researchers to be proactive in digital curation and feel confident to continue developing these skills.